The Gender Wage Gap in Developed Countries - Astrid Kunze (Center for Economic Studies and ifo Institute (CESifo), 2017)
Despite the increased attachment of women to the labour force in nearly all developed countries, a stubborn gender pay gap remains. This chapter provides a review of the economics literature on the gender wage gap, with an emphasis on developed countries. We begin with an overview of the trends in the gender differences in wages and employment rates. We then review methods used to decompose the gender wage gap and the results from such decompositions. We discuss how trends and differences in the gender wage gap across countries can be understood in light of non-random selection and human capital differences. We then review the evidence on demand-side factors used to explain the existing gender wage gap and then discuss occupational segregation. The chapter concludes with suggestions for further research.
Keywords: J16; J24; J31; J71; 330; wages; gender wage gap; wage differentials; labor force participation; discrimination; human capital investment; non-random selection; developed countries